Big data and management: From the Editors - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2014)
Big data is everywhere. In recent years, there has been an increasing emphasis on big data, business analytics, and "smart" living and work environments. Though these conversations are predominantly practice driven, organizations are exploring how large-volume data can usefully be deployed to create and capture value for individuals, businesses, communities, and governments (McKinsey Global Institute, 2011). Whether it is machine learning and web analytics to predict individual action, consumer choice, search behavior, traffic patterns, or disease outbreaks, big data is fast becoming a tool that not only analyzes patterns, but can also provide the predictive likelihood of an event.